Sedimentary environment evolution and provenance analysis of northwestern Liaodong Bay from the Middle Pleistocene. (10th July 2021) - Wang, Zhonglei; Zheng, Hongbo; Mei, Xi; Meng, Xiangjun; Xu, Tingting; Wang, Zhongbo; Mi, Beibei; Lan, Xianhong; Wang, Feifei; Wang, Shuang; Sun, Jun; Shang, Luning
Abstract: The environmental evolution and provenance of the sediments since 1.2 Ma penetrated by the borehole of JXC-1 in Northwestern Liaodong Bay are studied in this paper using the data from accelerator mass spectrometry 14 C dating, optically-stimulated luminescence dating, paleomagnetic dating, qualitative and quantitative analysis of benthic foraminifera, and the geochemistry analysis. Based on regional stratigraphic correlation, the evolution of sedimentary environment and provenance are discussed. The study suggests that large-scale transgression began by the end of Middle Pleistocene, and invaded into this region for three times from Late Middle Pleistocene to Holocene, in MIS 7, MIS5, and MIS1, that is in consistent with the global pattern of sea level changes. The results of this study are different from previous researches in the Bohai Sea, which found three times of transgressions in MIS5, MIS3, and MIS1 respectively. There are two possibilities, either no transgression in the Bohai Sea, or the transgression did not enter Liaodong Bay during the time of MIS3. Provenance analysis shows that the northwest of Liaodong Bay is a mixed depositional area. Sediments are mainly sourced from the Yellow River, Liaohe River (formerly Shuangtaizi River) and Daliao River. During the three marine phases, the sediments of the JXC-1 borehole came mainly from the Yellow River characterized by high content of CaO, and deposited under the control of Bohai Sea circulation and coastal currents. The sediments in depths of 36.00–46.00 m and 58.20–70.30 m of the borehole are high water level lacustrine sediments, mainly came from the Yellow River. However, the sediments in depths of 46.00–58.20 m are mainly brought in by the Liaohe and Daliao rivers. All these studies suggest that the sediments coming from the Yellow River may be distributed northward up to 40.5°N. As a major conclusion different from previous understandings, this paper provides an important reference for the evolution of the sedimentary environment and the provenance of the Late Quaternary deposits of the Bohai Sea.